Sensor network design for the estimation of spatially distributed processes - Uciński, Dariusz; Patan, Maciej (1975- ) (Zielona Góra: Uniwersytet Zielonogórski)
In a typical moving contaminating source identification problem, after some type of biological or chemical contamination has occurred, there is a developing cloud of dangerous or toxic material. In order to detect and localize the contamination source, a sensor network can be used. Up to now, however, approaches aiming at guaranteeing a dense region coverage or satisfactory network connectivity have dominated this line of research and abstracted away from the mathematical description of the physical processes underlying the observed phenomena
Keywords: optimal experiment design; parameter estimation; sensor network; source identification